Intracellular vorinostat accumulation and its relationship to histone deacetylase activity in soft tissue sarcoma patients - Burhenne, Jürgen; Liu, Lu; Heilig, Christoph E.; Meid, Andreas; Kasper, Bernd; Haefeli, Walter E.; Mikus, Gerd; Egerer, Gerlinde (Cancer chemotherapy and pharmacology, 2017)
PurposeIn the regulation of chromatin-structure and histone function, histone deacetylases (HDACs) are key enzymes and thus modulators of epigenetic regulation and gene expression. Accesses of the HDAC inhibitor vorinostat to intracellular compartments are essential to exert epigenetic effects.MethodsIn ten sarcoma patients receiving oral Zolinza (400 mg qd) vorinostat concentrations in plasma and peripheral blood mononuclear cells (PBMCs) were quantified using validated LC/MS/MS assays to determine intracellular and extracellular pharmacokinetic data. Cellular HDAC activity was evaluated using a fluorogenic assay. Concentration-response relationships were established between intracellular and extracellular vorinostat concentrations and HDAC inhibition in PBMCs.ResultsPharmacokinetics of vorinostat and its two main inactive metabolites were determined over 8 h in plasma and PBMCs. Steady state AUCs (±SD) and T1/2 (±SD) were calculated to 4.61 ± 0.87 h µM and 1.73 ± 0.69 h (plasma) and 15.2 ± 9.03 h µM and 5.30 ± 4.27 h (PBMCs). Intracellular accumulation of vorinostat was determined together with prolonged vorinostat elimination in PBMCs. Cellular HDAC inhibition increased parallel with vorinostat concentrations in plasma and PBMCs. For effective inhibition of cellular HDACs (IC50) vorinostat concentrations of 0.05 µM in plasma and 0.17 µM in PBMCs were necessary.ConclusionHDAC inhibition closely followed intracellular vorinostat concentrations and was short-lasting, which may contribute to the limited efficacy seen with vorinostat in solid tumors so far.